Constraints in Implementation of Green Building Projects in Malaysia: A Short Review - Hassan, Azrul; Mohd Asharuddin, Syazwani; Sukaimy, Mohd Farhan (Emerging Advances in Integrated Technology, 2023)
Green building (GB) is the foundation of sustainable construction and a part of promoting environmental conservation. Bringing change to the building construction industry requires multiple efforts from various angles especially to overcome any resistances in the form of technology, human aspects, financial and resources. The transition from conventional to sustainable approach consumes time as it requires changes from different facets in the industry ranging from individual, organizational to industry level. In Malaysia, there are various efforts to bring green into the industry but the progress is low moderate. The current review identified the major constraints that hinder a faster progress for green buildings development in Malaysia which include high initial cost, lack of knowledge and awareness among public and industry players, challenges in technology and expertise as well as lack of government enforcement and incentives. The outcomes of this paper will assist in enhancing and improving the sustainable practice in Malaysian’s construction industry for the betterment of life for sustainable communities.